Association of secondhand smoke exposure during pregnancy with left ventricle structure and function in offspring at 4 years old: a prospective birth cohort study - Bo Wang; Yongxuan Peng; Hualin Wang; Zhikang Xu; Bowen Du; Yiwei Niu; Zhuoyan Li; Zhi Wang; Qianchuo Wang; Caifang Xu; Shengju Yin; Yanan Lu; et al. (BMC Pregnancy and Childbirth)
Abstract Background The association of secondhand smoke exposure during pregnancy with childhood cardiac alterations remains insufficiently elucidated. This study aims to explore the correlation between maternal passive smoking during gestation with cardiac structure and function of offspring. Methods 1089 mother-offspring pairs from the Shanghai Birth Cohort were included. Information on secondhand smoke exposure during each trimester of pregnancy and baseline characteristics was documented during pregnancy via structured questionnaire. Subsequent follow-up assessments, encompassing anthropometric information and echocardiographic evaluation, were conducted from 2018 to 2021, when the children were 4 years old. Multiple linear regressions models were used to explore the association of secondhand smoke exposure during pregnancy with left ventricular measurements in early childhood. Results Secondhand smoke exposure during pregnancy was correlated with increased left ventricle (LV) internal diameter in diastole [LVIDd; β = 0.38, 95%CI: (0.06, 0.70)] and in systole [LVIDs; β = 0.28, 95%CI: (0.02, 0.54)] adjusted for maternal and child characteristics. Specifically, maternal passive smoking in early pregnancy (≤ 12 weeks of gestation) showed a positive association with LV internal diameter in diastole [LVIDd; β = 0.46, 95%CI: (0.14, 0.79)], in systole [LVIDs; β = 0.35, 95%CI: (0.09, 0.60)], end diastolic volume [LVEDV; β = 1.45, 95%CI: (0.26, 2.63)] and end systolic volume [LVESV; β = 0.68, 95%CI: (0.18, 1.19)]. No significant association was observed between secondhand smoke exposure during pregnancy and LV function of offspring. Conclusion Secondhand smoke exposure during pregnancy was correlated with subclinical alterations in LV dimensions of offspring, especially during the early stage of pregnancy. Further research is necessary to confirm our findings and to explore the long-term effect of these cardiac changes on later cardiovascular risks.